Erosion‐reducing effects of revegetation and fish‐scale pits on steep spoil heaps under concentrated runoff on the Chinese Loess Plateau. (6th July 2020) - Guo, Wenzhao; Kang, Hongliang; Wang, Wenlong; Guo, Mingming; Chen, Zhuoxin
Abstract: Massive spoil heaps, formed during production and construction activities, have suffered from severe soil erosion, leading to land degradation and damaging the environment. Fish‐scale pits (FSPs) and revegetation (RG) are the most common measures for controlling soil erosion on spoil heaps on the Loess Plateau. To evaluate the effects of FSPs and RG on concentrated runoff erosion, scouring‐erosion experiments were conducted on FSP plots, RG plots, and bare plots (the control) in the field on two types of spoil heaps: low gravel content in soil (LGS) and high gravel content in soil (HGS) at various inflow rates. Mass movement was the main cause of the considerable fluctuations in erosion rate and sharply increased the sediment concentration, which could exceed 800 kg m −3 and cause hyperconcentrated flows. Conversely, the FSP and RG treatments observably reduced the sediment concentration and erosion rate. The erosion‐reducing benefits (ERBs) of both the FSPs and RG treatments were significant. However, the ERB of the FSPs treatment was superior to that of the RG treatment under concentrated runoff, especially high‐intensity concentrated runoff. The ERB of the FSP treatment was on average 78.5% and 80.9% for the LGS and HGS, respectively. The ERB of the RG treatment was on average 36.4% and 56.5% for the LGS and HGS, respectively. The ERBs of the FSPs and RG treatments for the HGS were greater than those for the LGS. Moreover, gravel inhibited concentrated flow erosion. Our results provide important guidance for preventing soil erosion on abandoned spoil heaps in semiarid regions.